A REVIEW OF INERTIAL TENSOR MEASUREMENT RESEARCH - ZHAO He; MA WeiPing; YANG HongTao (Jixie qiangdu)
The inertia tensor is a measure of the rotational inertia of a rigid body when it rotates around a fixed point,and it is a key parameter in the design of control systems.The recent development of aircraft technology has made the need to accurately measure the inertia tensor of large⁃size irregular objects very urgent.Firstly,the research history and current problems of inertia tensor measurement were reviewed,and the measurement principles of methods such as the torsion pendulum method,the compound pendulum method,the energy method,and the parameter method were discussed respectively.Secondly,the issues such as the sources of measurement errors and error compensation that need to be faced when these measurement methods measure the inertia tensor of large⁃size irregular bodies were explored.Finally,the development history of inertia tensor measurement and point out the current problems and the follow⁃up research directions was summarized.